BATIK AS A MEDIUM FOR STRENGTHENING CHARACTER: A QUALITATIVE STUDY OF THE IMPLEMENTATION OF P5 LOCAL WISDOM - Ali Mas'ud; Sa'dun Akbar; Mardhatillah Akbar; M. Anas Thohir; Surayanah (Universitas Islam Negeri Mataram, 2025)
This study explores the implementation of the Pancasila Student Profile Strengthening Project (P5) with the local wisdom theme at UPT SD Negeri Pojok 01 Garum, Blitar. Using a qualitative descriptive approach, data was gathered through observation, interviews with fourth-grade teachers, and documentation. Findings reveal that P5 implementation follows five stages: introduction, contextualization, action, reflection, and follow-up, with a focus on Blitar batik. The project positively impacted students' cognitive development in understanding batik motifs, psychomotor skills in practicing tie-dye batik-making, and affective aspects by fostering collaboration and creativity. Analyzing students’ developmental progress showed notable improvements in creativity and independence. However, challenges such as time constraints and limited resources were identified. The study recommends optimizing schedules, expanding learning resources, and applying differentiated approaches. In conclusion, P5 with the local wisdom theme significantly strengthens students’ character in accordance with the Pancasila Student Profile while fostering appreciation for local culture.